Case Report: Transoral Penetrating Medullocervical Injury by a Chopstick in Three Cats - Nakano, Yukiko; Nozue, Yuta; Nakata, Kohei; Fujioka, Toru; Sakai, Yoichi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2020)
This case series describes transoral penetrating or contusive medullocervical injury by a wooden chopstick in three young cats presenting with acute tetraparesis. CT revealed that remnant fragments of a wooden chopstick penetrated the atlantooccipital space in cases 1 and 2. The remnant fragments were visualized clearly on CT under the bone window setting. MRI revealed a hyper-intense lesion in the spinal cord parenchyma at the level of C1 on T2-weighted images in case 3. Tetraparesis improved after surgical removal of the remnant fragment in case 2 and with supportive care in case 3.